A rose is a rose: naevoid manifestations blur the boundary between naevus and classical gene defect in focal dermal hypoplasia. (1st March 2019) - Traupe, H.
Abstract: Linked Article: Heinz et al. Br J Dermatol 2019; 180 :657–661 .